INSTITUTIONAL FRAMEWORK FOR IGBO APPRENTICESHIP SCHEME: AN ENTREPRENEURSHIP MODEL TO CURBING POVERTY IN NIGERIA - Onukwube Tobenna, (ADVANCED INTERNATIONAL JOURNAL OF BUSINESS, ENTREPRENEURSHIP AND SME'S (AIJBES), 2022)
Poverty is a societal bane leading to numberless social vices hampering justification of socio-economic development of any country. This malaise is variously addressed with entrepreneurship models, which include ‘Igbo Apprenticeship Scheme’, an age long practice which is more relevant in the contemporary economic challenges. However, it lacks institutional framework. These backdrops propelled this article to explore institutional framework for Igbo apprenticeship scheme as an entrepreneurship model to curbing poverty in Nigeria. This broad objective also defined the scope and limitation of the study. The research design and methodology was doctrinal approach, using exposition and analysis. The main sources of data collection were various related materials, both from the conventional library and e-library, including observable and life experiences. The summary of findings observed that Igbo apprenticeship scheme is a viable tool for curbing poverty and boosting Nigeria’s socio-economic development. Therefore, it was recommended, among others, that the Nigerian Government, in partnership with the major stakeholders in the Igbo entrepreneurship, should develop a workable policy and institutional framework for effective implementation of the scheme and as a prototype for easy adoption by other ethnic groups in Nigeria and beyond. Finally, this article is significant to all stakeholders in the areas of practical increase of participants and beneficiaries, curbing managerial anarchy and abuse of the process, as well as forming a theoretical policy that can be leverage on.